Existential anxiety, psychological flexibility, and deep resilience to climate crises - Weems, Carl F.; Poleacovsch, Cristina; Feinstein, Scott; Nartey, Marcus (Frontiers in Psychology, 2025)
Concerns and uncertainty about the viability of continued existence on the planet are central to the urgency of the climate crisis and can be contextualized within the philosophical idea of existential anxiety. The goal of this conceptual analysis is to outline how existential anxiety and psychological flexibility may help in understanding reactions to climate crises and thereby facilitate what has been termed “deep resilience.” This paper offers a definition of deep resilience that may be operationalized and measured, incorporating the concepts of existential anxiety and psychological flexibility. Simply put, deep resilience is multilayered, multiscale flexibility and adaptation to existential threat. Broadly, deep resilience involves flexible adaptation at the individual, family, community, societal, and geographical scales in response to existential threats to individuals, families, communities, societies, geographical regions, and the planet itself. The paper explores the conceptual and empirical foundations for these concepts as a potential basis for defining, acting toward, and actualizing deep resilience. Examples from the empirical literature spanning psychological, climate-related, and political domains are discussed, with avenues for future research and policy noted.